Making Transition Easier: Year 12 Students get a Head Start on University Education - Bolt, Susan; Graber, Mark (Common Ground Publishing, 2010)
The transition of students from high school into university is challenging; so, creative and imaginative thinking is needed to design learming experiences to support students' transition from one educational sector to another: According to research conducted by Professor Sally Kift, transition, diversity and design are three of the six critical aspects of curriculum design which lead to a successful first year experience for students entering university. Im an effort to meet this challenge, lecturers in the School of Information Systems at Curtin Business School (CBS) have developed an innovative learning experience in which Applied Information Technology students are given the opportunity to complete a first year university Business Information Systems unit whilst in their final year of high school.The case study research presented in this paper is the result of the evidence gathered from student feedback and lecturer's reflectiions on the learning and teaching experience, as well as a review of literature pertinent to curriculum design. As a result of this research, it was found that high school students received free tuition and credit for completion of a university unit, as well as exposure to university standards while in their final year of high school. This experience motivates students to achieve in their Tertiary Entrance Examination and supports their transition into the Bachelor of Commerce course. As a result of the success of programs such as this, CBS has broadened its scope and in 2010 will offer a wider range of programs through its Year 12 Excelerate initiative.